2011
DOI: 10.1002/nme.3134
|View full text |Cite
|
Sign up to set email alerts
|

A quasicontinuum methodology for multiscale analyses of discrete microstructural models

Abstract: SUMMARYMany studies in different research fields use lattice models to investigate the mechanical behavior of materials. Full lattice calculations are often performed to determine the influence of localized microscale phenomena on large-scale responses but they are usually computationally expensive. In this study the quasicontinuum (QC) method (Phil. Mag. A 1996; 73:1529-1563) is extended towards lattice models that employ discrete elements, such as trusses and beams. The QC method is a multiscale approach tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 31 publications
0
64
1
Order By: Relevance
“…First, this leads to a large number of degrees of freedom (DOFs) making the system of equations computationally expensive to solve. Secondly, the construction of the system of equations is computationally expensive because all lattice points must be visited for this (Beex et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…First, this leads to a large number of degrees of freedom (DOFs) making the system of equations computationally expensive to solve. Secondly, the construction of the system of equations is computationally expensive because all lattice points must be visited for this (Beex et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The QC method was originally developed for the reduction of atomistic lattice models by Tadmor et al (1996a) and has been widely used to investigate phenomena such as intergranular fracture (Miller et al, 1998) and nanoindentation (Tadmor et al, 1996b;Knap and Ortiz, 2001;Kulkarni et al, 2008). In a previous study (Beex et al, 2011) the applicability of the QC method has been demonstrated for structural lattice models of fibrous materials that employ elastic trusses. An overview of several QC frameworks is given by Miller and Tadmor (2002).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations